Pengaruh ekstrak nanas (ananas comosus) sebagai agensia bating terhadap kekuatan tarik dan suhu kerut kulit kelinci lokal samak nabati - Widowati, Titik Purwati; Setyawardani, Triana; Hastuti, Dwi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2002)
The aims of experiment were to find out the effects of concentration of pineapple extract, bating time and their interactions on tensile strength and shrinkage temperature of local rabbit skin, which was tanned by vegetable tanning agent. The materials of this experiment were 27 rabbit skins used as bating object. The experimental design used was completely randomized design (CRD) with factorial treatments 3 x 3. The results of analysis showed that concentration of pineapple extract, bating time and their interactions were not significantly affect (P < 0,05) on tensile strength and shrinkage temperature . The average of the tensile strength at this experiment was 157,394 kg/cm2 and fulfilled the requirement of SNI. 06-0463-1989: Kulit Lapis Doma/Kambing Samak Kombinasi (Krom Nabati), Mutu dan Cara Uji, and shrinkage temperature was 79,70oC that means fulfilled Nayudamaâs (1978) did requirement.Â Key words : pineapple slurry, tensile strength, shrinkage temperature, rabbit skin.